Análisis comparativo de la información expuesta en los medios de comunicación (Redes Sociales y TV Nacional) en el caso manifestaciones Ecuador 2019 - Castro Cedeño, Karen Liseth (2020)
A comparative analysis leads to a thorough study in this case of two objects within a phenomenon, such as social networks and national TV within the manifestations raised in October 2019 in Ecuador. Both are important and influential media in the formation of the opinion of every citizen, these media are characterized by sharing the news of the demonstrations; one in a short way in real time and the other in depth going to the scene, also share images, audio and video things that resemble them. They differ because social networks exercise journalism independently and any user plays the role of communicator, journalism within national television is made by professionals who apply studies and are based according to what their media says and to the laws of the LOC. In the survey that was carried out on a group of people, the popularity of social networks was evident, nowadays who does not get to have a social network if they are the most used platforms to interact and create advertisements, mostly society disagreed with the measures taken by the government reason why the protests began, after eleven days of confrontation between members of the public force and indigenous movements accompanied by students, youth and workers managed to repeal the decree, which in the first instance said that the fuel subsidy was eliminated.